Hukum Bunga Bank dalam Persepsi Nasabah yang Tinggal di Pedesaan dan Perkotaan (Studi Kasus di Kudus Jawa Tengah) - Inna Faiziatal Ngazizah; Muhammad Zainal Abidin (SALIHA: Jurnal Pendidikan & Agama Islam, 2020)
Diversity can occur in rural or urban areas. Rural and urban communities have very different characteristics. Rural communities are characterized by brotherhood, closeness and a life influenced by nature. Meanwhile, urban communities have the characteristics of selective, self-oriented, universalism, achievement and heterogeneous. Different types of people influence their perceptions of life. The perception referred to in this research is the perception in economics. The main objective of this study is to determine the law of bank interest from the perspective of customers who live in rural and urban areas. This study examines problems, procedures, certain situations, everything related, activities, attitudes, views, processes and effects of an event that occurs in society and the type of research in this research is field research when viewed from a perspective. places using 11 respondents obtained using quota sampling, purposive sampling and side incidental. The results showed that the residence of Islamic bank customers did not affect the perception of the law of bank interest. This is formulated through the research results that have been achieved as a form of answer to the problem formulation.